Fundamentals of fluid mechanics - Munson, Bruce Roy 1940- (John Wiley & Sons, 1998)
This students solutions manual accompanies the main text. Each concept of fluid mechanics is considered in the book in simple circumstances before more complicated features are introduced. The problems are presented in a mixture of SI and US standard units.